Pengambilan Keputusan Multikriteria Pemilihan Produk Diskon Berbasis AHP pada Toko Ritel XYZ Subah - Nabela, Harlinda Rasvi (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Selecting discounted products is a crucial operational decision in retail businesses because it directly impacts sales and inventory management. This study attempts to develop a decision-making model for selecting discounted products using the Analytical Hierarchy Process (AHP) method in XYZ Subah Retail Store. Criteria considered include time, product type, product tenure, competition, inventory, and promotions. Products include food and beverages, home care, and fashion. The results show that home care products have the highest priority. Of the various criteria, time of sale and product characteristics are the primary factors in decision-making, with sub-criteria related to major holidays and product functionality. This model is expected to assist retail management in creating objective and organized discount policies.